Jobs - Stern, Joshua Michael; Kutcher, Ashton; Modine, Matthew; Hulme, Mark; Whiteley, Matt; The Jobs Film. (United States : The Jobs Film, 2013)
The story of Steve Jobs' ascension from college dropout into one of the most revered creative entrepreneurs of the 20th century. The extraordinary story of Steve Jobs, the original innovator and ground-breaking entrepreneur who let nothing stand in the way of greatness. The film telss the epic and turbulent story of Jobs as he blazed a trail that changed technology and the world forever.
Director of photography, Russell Carpenter ; music, John Debney ; editor, Robert Komatsu.
Ashton Kutcher, Matthew Modine, Dermot Mulroney, Josh Gad, Lesley Ann Warren, Lukas Haas, J.K. Simmons, Ron Eldard, James Woods, Ahna O'Reilly, Victor Rasuk, John Getz.
DVD format, DVD-5, PAL, 16x9 Fullframe (1.78:1), Region 3, Dolby Digital 2.0.
In English with optional Malay, English and Chinese subtitles.
Title from disc label.
Keywords: Jobs, Steve, -- 1955-2011 -- Drama; Apple Computer Inc. -- History -- Drama; Businesspeople -- United States -- Drama; Computer industry -- United States -- Drama; Biographical films